Lung Cancer Associated with Neurofibromatosis Type I. (28th February 2013) - Oikonomou, Anastasia; Mikroulis, Dimitrios; Mintzopoulou, Paraskevi; Lukman, Lawal; Prassopoulos, Panos
Abstract : Lung cancer associated with neurofibromatosis type I is considered very rare, and only a few case reports have been described in the literature. There is some evidence that a genetic linkage between neurofibromatosis and carcinogenesis in the lung may exist. We present a 42-year-old female, lifetime nonsmoker with a known history of neurofibromatosis type I, free of respiratory symptoms, who underwent a low-dose HRCT of the lungs to investigate any occult interstitial lung changes. A solitary ill-defined nodule of a ground-glass opacity was detected incidentally in the middle lobe with no associated lymphadenopathy or metastatic disease. Several thin-walled lung cysts were also seen in the lower lobes. Histological analysis of the nodule after middle lobectomy revealed well-differentiated adenocarcinoma. The patient did not receive systemic chemotherapy or radiotherapy. She was free of disease on 18-month followup.